Enhancing music education in the Peruvian Amazon: a call for urgent action - Prados Bravo, Saray; Rolando, Claudia (Frontiers in Education, 2023)
This study focuses on music education in the Peruvian educational system, specifically in the Alto Amazonas region. Through qualitative research methods such as participant observation, video recordings, documentary analysis and questionnaires, the study assesses the state of music education and music teacher education, evaluates the musical training of individuals in jungle populations, and explores strategies for preserving Amazonian folklore. The findings reveal a lack of emphasis on music in the curriculum, inadequate teacher training, and a need to protect and revitalize folklore. Recommendations are made to address these issues, including curriculum development, teacher training, and revitalization of traditional music in classrooms. The study emphasizes the importance of integrating music into various subjects, increasing access to university music courses, conducting research, and supporting ethnomusicological studies. Urgent action is urged to improve music education, preserve cultural heritage, and provide comprehensive musical education for students in the Peruvian Amazon.